HUBUNGAN STATUS GIZI IBU HAMIL DENGAN BERAT BADAN LAHIR RENDAH (BBLR) DI RUMAH SAKIT ST. MADYANG KOTA PALOPO - Hamalding, Hermawati; Oka, Irmayanti A.; Fitriani, Sri Ika (UNM Environmental Journals, 2023)
LBW continues to be a significant public health problem globally because of its short-term and long-term effects on health. One way to prevent low birth weight babies (LBW) is by improving the nutritional status of pregnant women. The purpose of this study was to determine the relationship between the nutritional status of pregnant women and low birth weight at St. Madyang City of Palopo. This type of research is an analytic observational study with correlation studies. The time approach used is a cross sectional study. The population in this study were all pregnant women who gave birth at St. Madyang City of Palopo as many as 99 people. The sample in this study were pregnant women who gave birth at St. Madyang City of Palopo as many as 99 people. In this study the sample was taken using total sampling. Data analysis using the Chi Square Test. The results showed that 16 respondents (16.2%) had KEK nutritional status and 83 respondents (83.8%) had normal nutritional status. Respondents who had LBW babies were 23 people (23.2%) and babies who were not LBW were 76 people (76.8%). There is a relationship between the nutritional status of pregnant women and low birth weight (LBW) at St. Madyang City of Palopo, significant value p = 0.000 <α = 0.05. The conclusion in this study is that there is a relationship between the nutritional status of pregnant women and low birth weight (LBW) at St. Madyang City of Palopo. This research is expected to be used as a reference in improving MCH services at St. Madyang especially regarding the nutritional status of pregnant women and birth weight (BBL).